2022
DOI: 10.1111/jfbc.14189
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin gallate: Phytochemistry, bioavailability, utilization challenges, and strategies

Abstract: Epigallocatechin gallate (EGCG), a green tea catechin, has gained the attention of current study due to its excellent health‐promoting effects. It possesses anti‐obesity, antimicrobial, anticancer, anti‐inflammatory activities, and is under extensive investigation in functional foods for improvement. It is susceptible to lower stability, lesser bioavailability, and lower absorption rate due to various environmental, processing, formulations, and gastrointestinal conditions of the human body. Therefore, it is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 225 publications
(266 reference statements)
1
28
0
Order By: Relevance
“…EGCG and other catechins are highly enriched in green tea, and their daily intake is around 90-300 mg/day [81]. The beneficial effects of green tea on health have been known for millennia especially in Far East countries and modern science has demonstrated that EGCG is its predominant active molecule [82]. As for most flavonoids and polyphenols, it is nevertheless worth mentioning that their beneficial effects are not only a matter of ingested quantity, but rather of bioavailability.…”
Section: Epigallocatechin-3-gallatementioning
confidence: 99%
See 2 more Smart Citations
“…EGCG and other catechins are highly enriched in green tea, and their daily intake is around 90-300 mg/day [81]. The beneficial effects of green tea on health have been known for millennia especially in Far East countries and modern science has demonstrated that EGCG is its predominant active molecule [82]. As for most flavonoids and polyphenols, it is nevertheless worth mentioning that their beneficial effects are not only a matter of ingested quantity, but rather of bioavailability.…”
Section: Epigallocatechin-3-gallatementioning
confidence: 99%
“…Apart from more general beneficial effects on health of green tea extracts that are shared with other classes of flavonoids, such as the antioxidant, anti-inflammatory, antitumoral, antiviral, hypoglycemic and antiaging activities as recently summarized in details elsewhere [82], EGCG is endowed with positive outcomes on specific pathological mechanisms involved in neurodegeneration. Despite the very different clinical characteristics, AD and PD share many common pathological features, including the presence of a pro-inflammatory environment which is sustained and promoted by activated microglia and astrocytes, oxidative stress, the aggregation/precipitation/deposition of misfolded proteins, namely amyloidogenic -amyloid fragments (A1-42) and Tau protein in AD and -synuclein in PD, and dysregulation of the autophagy process, as recently brilliantly reviewed in [91].…”
Section: Epigallocatechin-3-gallatementioning
confidence: 99%
See 1 more Smart Citation
“…EGCG metabolites are excreted through both bile and urine. EGCG can be further reabsorbed from the intestine through the enterohepatic recirculation process [ 233 , 234 , 235 ].…”
Section: Nutraceuticalsmentioning
confidence: 99%
“…Likewise, it has been suggested that the ingestion of EGCG on an empty stomach may improve its systemic absorption [ 240 ]. Moreover, the structural modification of EGCG by methylation, acyclization, or glycoside modification seems to allow the management of its premature degradation and reduced absorption rate [ 228 , 233 ]. Finally, one promising approach to protect EGCG against unfavorable gastrointestinal conditions and improve its bioavailability includes the design of nanocarriers.…”
Section: Nutraceuticalsmentioning
confidence: 99%